Link quality multipath based routing scheme for underwater wireless sensor network - Mukhtiar Ahmed, 1969-; Mazleena Salleh, supervisor; Fakulti Kejuruteraan. Sekolah Komputeran (Johor Bahru, Johor : Universiti Teknologi Malaysia, 2018)
Thesis (Doktor Falsafah (Sains Komputer)) - Universiti Teknologi Malaysia, 2018